OX40 Expression in Eosinophils Aggravates OVA-Induced Eosinophilic Gastroenteritis - Xu, Longwei; Tian, Dan; Zhou, Minsi; Ma, Jiuyue; Sun, Guangyong; Jin, Hua; Li, Mingyang; Zhang, Dong; Wu, Jing (Frontiers in Immunology, 2022)
Background & Aims: Eosinophils are the main inflammatory effector cells that damage gastrointestinal tissue in eosinophilic gastrointestinal diseases (EGIDs). Activation of the OX40 pathway aggravates allergic diseases, such as asthma, but it is not clear whether OX40 is expressed in eosinophils to regulate inflammation in EGIDs. In this study, we assessed the expression and effect of OX40 on eosinophils in WT and Ox40-/- eosinophilic gastroenteritis (EGE) mice. Methods: Eosinophil infiltration, ovalbumin (OVA)-specific Ig production, OX40 expression and inflammatory factor levels in the intestine and bone marrow (BM) were investigated to evaluate inflammation. Results: We confirmed that OVA-challenged mice produced high levels of Ox40, Mbp, Ccl11, Il5, Il4, Il13, and Il6 mRNA and a low level of Ifng mRNA in the intestine. Increased eosinophils were observed in intestinal and lymph tissues, accompanied by significantly upregulated OX40 and Type 2 cytokine production in eosinophils of EGE mice. Ox40 deficiency ameliorated OVA-induced inflammation, eosinophil infiltration, and cytokine production in the intestine. Consistently, Ox40-/- eosinophils exhibited decreased proliferation and proinflammatory function. The stimulation of the agonistic anti-OX40 antibody, OX86, stimulation promoted the effect of OX40 on eosinophils. The present study also showed that Ox40 deficiency dampened the Traf2/6-related NF-κB signaling pathway in eosinophils. Conclusions: OX40 may play a critical role in the progress of OVA-induced EGE by promoting the maturation and function of eosinophils via the Traf2/6-related NF-κB signaling pathway.